REPRESENTASI GENDER DALAM MEDIA SOSIAL INSTAGRAM TERHADAP PERSEPSI REMAJA TENTANG IDENTITAS GENDER DI DESA JE’NEMADINGING - Massuanna, Muhammad Watif; Torro, Supriadi; R, Nurazizah Rahmi (Universitas Negeri Makassar, 2024)
This research aims to find out 1) How gender representation on the social media Instagram influences the way teenagers understand their own gender identity among teenagers in Je'nemadinding Village, Gowa Regency and 2) What is the impact of the construction of reality through the social media Instagram among teenagers in Je Village 'nemadinding, Gowa Regency. This type of research is qualitative research with a descriptive approach. The informants in this study were 10 people who were selected based on purposive sampling techniques. Data collection techniques in this research used observation, interview and documentation techniques. The data analysis technique in this research uses data reduction techniques, data presentation and drawing conclusions. The data validation technique in this research uses the Member Check technique, which is a data collection technique by re-interviewing informants so that it is said to be valid. The results of this research show that: 1) Gender representation on the social media Instagram influences the way teenagers understand their own gender identity. Among teenagers in Je'nemadinging Village, Gowa Regency, there are several factors, namely, exposure to gender content on Instagram, understanding and perceptions about gender. , and the influence on self-image and self-confidence as well as self-identity. And 2) The impact of reality construction through Instagram social media among teenagers in Je'nemadinging Village, Gowa Regency is divided into two impacts, namely positive impacts and negative impacts, namely: positive impacts consist of: 1). There is educational content presented by content creators, 2). The emergence of various inspirations and motivations from various content that shows goodness, 3). The existence of online communities created by influencers can help teenagers get emotional and motivational support, 4). The existence of social connections on Instagram allows teenagers to connect with their friends, even from a distance, 5). The emergence of various self-development which provides space for teenagers to express themselves, and 6). Increasing teenagers' technology and digital skills. Meanwhile the negative impacts are: 1). There are social comparisons held by influencers or other individuals who present their ideal lives which often lead to feelings of not being good enough, insecurity, stress and anxiety, 2). There is pressure to always be perfect on social media which can cause stress and anxiety if teenagers feel unable to meet these expectations, 3). The large need for validation among teenagers, 4). There are health problems for individuals with excessive use of social media, 5). There is a lot of Instagram content that shows a very idealistic and unrealistic life, 6). There is exposure to negative content so that teenagers may be exposed to negative content such as cyberbullying, body shaming, or content that promotes dangerous behavior, 7). There is a decrease in face-to-face social interactions, when teenagers become dependent on social media, 8). There is an effect of decreasing productivity and 9). A lot of time is wasted when surfing Instagram.